2015
DOI: 10.5194/acp-15-7247-2015
|View full text |Cite
|
Sign up to set email alerts
|

Low hygroscopic scattering enhancement of boreal aerosol and the implications for a columnar optical closure study

Abstract: Abstract. Ambient aerosol particles can take up water and thus change their optical properties depending on the hygroscopicity and the relative humidity (RH) of the surrounding air. Knowledge of the hygroscopicity effect is of crucial importance for radiative forcing calculations and is also needed for the comparison or validation of remote sensing or model results with in situ measurements. Specifically, particle light scattering depends on RH and can be described by the scattering enhancement factor f (RH), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 72 publications
1
55
0
Order By: Relevance
“…Understanding the factors controlling the change in extinction or scattering as a function of RH, known as f (RH), is important for evaluating remote sensing measurements (e.g., Brock et al, 2016;Crumeyrolle et al, 2014;Esteve et al, 2012;Ferrare et al, 1998;Hegg et al, 1993;Kotchenruther et al, 1999;van Donkelaar et al, 2015;Voss et al, 2001;Zieger et al, 2011Zieger et al, , 2012Ziemba et al, 2012), aerosol direct radiative forcing calculations (e.g., Attwood et al, 2014;IPCC, 2013;Kahn, 2011;Koloutsou-Vakakis et al, 1998;Nemesure et al, 1995), and atmospheric visibility estimates (e.g., Charlson et al, 1967;Malm et al, 2000). In general, particles composed primarily of organic material and dust are less hygroscopic Petters and Kreidenweis, 2007;Zieger et al, 2015), while those that are predominantly inorganic take up water more readily (e.g., Petters and Kreidenweis, 2007;Quinn et al, 2005). Particles may exhibit sharp phase transitions as they deliquesce, as well as hysteresis as they effloresce, especially for inorganic compositions (e.g., Santarpia et al, 2005;Tang, 1996;Zieger et al, 2014).…”
Section: A Brock Et Al: Aerosol Optical Properties In the Southementioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the factors controlling the change in extinction or scattering as a function of RH, known as f (RH), is important for evaluating remote sensing measurements (e.g., Brock et al, 2016;Crumeyrolle et al, 2014;Esteve et al, 2012;Ferrare et al, 1998;Hegg et al, 1993;Kotchenruther et al, 1999;van Donkelaar et al, 2015;Voss et al, 2001;Zieger et al, 2011Zieger et al, , 2012Ziemba et al, 2012), aerosol direct radiative forcing calculations (e.g., Attwood et al, 2014;IPCC, 2013;Kahn, 2011;Koloutsou-Vakakis et al, 1998;Nemesure et al, 1995), and atmospheric visibility estimates (e.g., Charlson et al, 1967;Malm et al, 2000). In general, particles composed primarily of organic material and dust are less hygroscopic Petters and Kreidenweis, 2007;Zieger et al, 2015), while those that are predominantly inorganic take up water more readily (e.g., Petters and Kreidenweis, 2007;Quinn et al, 2005). Particles may exhibit sharp phase transitions as they deliquesce, as well as hysteresis as they effloresce, especially for inorganic compositions (e.g., Santarpia et al, 2005;Tang, 1996;Zieger et al, 2014).…”
Section: A Brock Et Al: Aerosol Optical Properties In the Southementioning
confidence: 99%
“…Particles may exhibit sharp phase transitions as they deliquesce, as well as hysteresis as they effloresce, especially for inorganic compositions (e.g., Santarpia et al, 2005;Tang, 1996;Zieger et al, 2014). Particles dominated by organic compounds are more likely to present more gradual hygroscopic growth with increasing RH without evident phase transition behavior (e.g., Carrico et al, 2005;Zieger et al, 2015).…”
Section: A Brock Et Al: Aerosol Optical Properties In the Southementioning
confidence: 99%
“…Although the behavior of the backscatter coefficient at enhanced RH is expected to differ from the scattering coefficient, a qualitative comparison can be performed due to the scarcity of backscatter-related γ values in the literature. For example, using in situ techniques, Zieger et al (2015) reported a low scattering enhancement of boreal aerosol in Hyytiälä (Finland) (γ 525 = 0.25) related to the high contribution of organic aerosols at this site that contribute to decreasing the hygroscopic enhancement. At Cape Cod (USA), Titos et al (2014) reported significantly lower γ values for polluted aerosols (γ 550 = 0.4 ± 0.1) compared with marine aerosols (γ 550 = 0.7 ± 0.1).…”
Section: F λ β (Rh) Measured and Retrieved By Combining In Situ Data mentioning
confidence: 99%
“…The spatial distribution of the carbon budget shows considerable variation, and substantial areas, particularly in permafrost regions and in disturbed forests, display both sink and source behaviour. The already clearly observable greening of the Arctic is going to have large consequences on the carbon sink in the upcoming decades (Myneni et al, 1997;Zhou et al, 2001), although future predictions are uncertain. The net ecosystem carbon budget (NECB) or net biome production (NBP) are usually a sensitive balance between carbon uptake through forest growth, ecosystem heterotrophic respiration, and carbon release during and after disturbances such as fire, insect outbreaks, or weather events, e.g.…”
Section: Carbon Cyclementioning
confidence: 99%
“…Hollstein and Fisher, 2014), or instruments providing multiple viewing algorithms such as MISR (Nelson et al, 2013) or AATSR (Virtanen et al, 2014). Another complication for aerosols may be the vertical variation of the physical and chemical properties, which renders it difficult to obtain closure between column and groundbased in situ measurements (Zieger et al, 2015, and references cited therein). Nevertheless, good progress has been made in aerosol retrieval, and column-integrated aerosol measurements (aerosol optical depth, AOD) from satellites and ground-based observations compare favourably (e.g.…”
Section: Main Pollutantsmentioning
confidence: 99%